A preliminary Result of the Comparative Research of the Curricula for the Preparation of Long-song Singers of the National Institute of Khukh Khot City and the University of Arts and Culture - Sainbayar, Uyanga; Tseren, Chuluuntsetseg (Mongolian Journal of Arts and Culture, 2023)
Researchers have emphasized that it is necessary to profound the study of the program for training professional singers, as a university education and to carry out the program in a traditional way as well as to direct towards training professional teachers. The purpose of the research is to determine the evidence for reforming the curriculum on the basis of the study of the theory and methodology of training professional singers. The theory books, research materials and curriculum for the preparation of long-song singers of the school of the music art of the MSUAC and the professional organizations which work out the curriculum and training programs of the branch school of the song art of the National Institute of Khukh Khot city of the Inner Mongolia were used. We concluded that it is necessary to update the training program for the development of the singing skills of the students who study in the field of long-song singing at the National Institute of Khukh Khot city of the IMAR through the study of the training theory and methodology of the preparation of the professional long-song singers and it is also significant to test and study its result. “Хөх хот” Үндэстний дээд сургууль болон Соёл урлагийн их сургуулийн мэргэжлийн уртын дуучин бэлтгэх сургалтын хөтөлбөрүүдийг харьцуулан судалсан урьдчилсан дүнгээс Хураангуй: Судлаачид их сургуулийн боловсрол болох мэргэжлийн уртын дуучдын сургалт ын хөтөлбөрийг гүнзгийрүүлэн судалж, хөтөлбөрийг уламжлалт байдлаар хэрэгжүүлэх, мөн мэргэжлийн багш нарыг сургахад чиглүүлэхийн чухлыг онцлон тэмдэглэсээр байна. Судалгааны зорилго нь мэргэжлийн дуучдыг сургах онол , арга зүйн судалгааг үндэслэн сургалт ын хөтөлбөрийг шинэчлэх үндэслэлийг тодорхойлоход оршино. Судалгаанд Монгол улсын Соёл урлагийн их сургуулийн Хөгжмийн урлагийн сургуулийн уртын дуучин бэлтгэхэд зориулсан хөтөлбөр болон Өвөр Монголын Хөх хотын үндэстний дээд сургуулийн дуу урлагийн салбар сургуулийн хөтөлбөр, сургалтын программ, онолын ном, судалгааны материал ыг ашигласан . Бид мэргэжлийн уртын дуу дуулаачдыг бэлтгэх сургалтын онол , арга зүйг судалж, Өвөр Монголын Хөх хотын үндэстний дээд сургуулийн уртын дуунд суралцаж байгаа оюутнуудын дуулах ур чадварыг хөгжүүлэх хөтөлбөрийг шинэчилж, түүний үр дүнг судлах нь чухал хэмээн үзлээ. Түлхүүр үг: сургалтын хөтөлбөр, урын са н, арга зүй, угсаата н, үнэт зүйл, суралцагч, урт ын дуу, дуучин